If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 6x + 9 Reorder the terms: -2 + 3x = 6x + 9 Reorder the terms: -2 + 3x = 9 + 6x Solving -2 + 3x = 9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -2 + 3x + -6x = 9 + 6x + -6x Combine like terms: 3x + -6x = -3x -2 + -3x = 9 + 6x + -6x Combine like terms: 6x + -6x = 0 -2 + -3x = 9 + 0 -2 + -3x = 9 Add '2' to each side of the equation. -2 + 2 + -3x = 9 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 9 + 2 -3x = 9 + 2 Combine like terms: 9 + 2 = 11 -3x = 11 Divide each side by '-3'. x = -3.666666667 Simplifying x = -3.666666667
| 18x+6x=300-150 | | 6(x-75)-4(x+64)=64-6(x-72) | | d=50(5) | | -(x-4)=2(5x+9) | | 9x-(215/3)=4x | | 2x+8+52+5x=180 | | x-2y=14-x-3y=-9 | | 4(2x+8)=-39+23 | | (88-75)+g=50 | | 5x+2x+3x=180 | | 12*1.4/1 | | 3(x+15)-2(-x+5)=-25 | | y-3.7=13.8 | | 4xsquared-7=9 | | six=-0.465 | | 26+4x+3+8=180 | | 9xu=81 | | 9g=7.38 | | 29r=319/36 | | sqr(2x-x^2+8)+sqr(2x-x^2+3)=-2x+x^2+6 | | sin(x)=-0.465 | | 8/9x-1/2=1/3 | | 8x-(87/2)=2x | | d=15(40) | | 5(x+2)+3(-x+4)=2 | | 2x+10=50000 | | 11x-4(x-4)=7x+14 | | cos(a)=0.64 | | xovery=2 | | -4x-6+x=-2x+x-3 | | 8n^2+3n-5=0 | | d=10(40) |